Can We Use Antibodies to Chlamydia trachomatis as a Surveillance Tool for National Trachoma Control Programs? Results from a District Survey. - Sheila K West; Beatriz Munoz; Jerusha Weaver; Zakayo Mrango; Laura Dize; Charlotte Gaydos; Thomas C Quinn; Diana L Martin (Public Library of Science (PLoS), 2016)
BACKGROUND:Trachoma is targeted for elimination by 2020. World Health Organization advises districts to undertake surveillance when follicular trachoma (TF) <5% in children 1-9 years and mass antibiotic administration has ceased. There is a question if other tools could be used for surveillance as well. We report data from a test for antibodies to C. trachomatis antigen pgp3 as a possible tool. METHODOLOGY:We randomly sampled 30 hamlets in Kilosa district, Tanzania, and randomly selected 50 children ages 1-9 per hamlet. The tarsal conjunctivae were graded for trachoma (TF), tested for C. trachomatis infection (Aptima Combo2 assay: Hologic, San Diego, CA), and a dried blood spot processed for antibodies to C. trachomatis pgp3 using a multiplex bead assay on a Luminex 100 platform. PRINCIPAL FINDINGS:The prevalence of trachoma (TF) was 0.4%, well below the <5% indicator for re-starting a program. Infection was also low, 1.1%. Of the 30 hamlets, 22 had neither infection nor TF. Antibody positivity overall was low, 7.5% and increased with age from 5.2% in 1-3 year olds, to 9.3% in 7-9 year olds (p = 0.015). In 16 of the 30 hamlets, no children ages 1-3 years had antibodies to pgp3. CONCLUSIONS:The antibody status of the 1-3 year olds indicates low cumulative exposure to infection during the surveillance period. Four years post MDA, there is no evidence for re-emergence of follicular trachoma.